2006
DOI: 10.1007/s00408-005-2594-8
|View full text |Cite
|
Sign up to set email alerts
|

Achieving Full-Dose, On-Schedule Administration of ACE Chemotherapy Every 14 Days for the Treatment of Patients with Extensive Small-Cell Lung Cancer

Abstract: Extensive small-cell lung cancer (SCLC) is commonly treated with multiple cycles of chemotherapy. Reducing the time interval between cycles of chemotherapy (dose-dense chemotherapy) may improve outcomes in the treatment of extensive SCLC, as it has in other chemosensitive malignancies. To evaluate the feasibility of dose-dense chemotherapy in patients with extensive SCLC, this study evaluates a dose-dense doxorubicin/cyclophosphamide/etoposide (ACE) regimen, supported by the once-per-cycle administration of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 29 publications
0
8
0
1
Order By: Relevance
“…Patient data from the remaining 22 studies that met the eligibility criteria were analyzed (Supplementary Table S1) [6][7][8][18][19][20][21][22][23][24][25][26][27][28][29][30][31].…”
Section: Studiesmentioning
confidence: 99%
“…Patient data from the remaining 22 studies that met the eligibility criteria were analyzed (Supplementary Table S1) [6][7][8][18][19][20][21][22][23][24][25][26][27][28][29][30][31].…”
Section: Studiesmentioning
confidence: 99%
“…In patients with SCLC, full-dose, on-schedule, dose-dense ACE chemotherapy was found to be feasible with pegfilgrastim support [65]. …”
Section: G-csf To Support Chemotherapy: New Datamentioning
confidence: 99%
“…In none of these trials was there evidence for a potential detrimental effect on neutropoiesis with the use of long-lasting G-CSF. Moreover, in the few trials in which the hematotoxic effects were shown for each separate chemotherapy cycle, no constellation was found in which neutropenia in cycle 2 was more pronounced than in the first cycle [34,40]. Thus, in all studies reported so far there is no evidence that the use of longacting G-CSF preparations in dose-dense settings leads to unexpected severe hematological toxicity.…”
Section: Use Of Long-acting Growth Factors In Dose-dense Chemotherapymentioning
confidence: 95%
“…Alternatively, it may be that the incidence of severe neutropenia was significantly higher in the study arm using longlasting G-CSF in 2-weekly chemotherapy protocols as compared to study arms using short-acting G-CSF in 2-weekly protocols or as compared to the study arms using pegfilgrastim in 3-weekly chemotherapy protocols. Although in most studies investigating dose-dense protocols these questions were not specifically addressed, these trials could demonstrate the safe and effective use of pegfilgrastim to support a variety of chemotherapy regimens with 14-day intervals for the treatment of early stage breast cancer [29][30][31][32][33][34][35][36][37][38][39], small cell lung cancer [40,41], non-small cell lung cancer [42], non-Hodgkin's lymphoma [43,44], Hodgkin's disease [45] and gastric cancer [46]. In none of these trials was there evidence for a potential detrimental effect on neutropoiesis with the use of long-lasting G-CSF.…”
Section: Use Of Long-acting Growth Factors In Dose-dense Chemotherapymentioning
confidence: 99%